ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN INDEKS PEMBANGUNAN MANUSIA (IPM) TERHADAP TINGKAT PENGANGGURAN - Wilujeng, Dwi; Prasetyia, Ferry (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Java Island provides the largest contribution to national income, so that Java Island has become the economic center in Indonesia. However, unfortunately, areas with high levels of income or economic growth actually contribute to high levels of unemployment. The aim of the research is to determine the effect of economic growth, the Human Development Index (HDI), District/City Minimum Wage (UMK), and population on the unemployment rate on the island of Java in 2017-2021. The research method used is the panel data analysis method with the Fixed Effect Model approach. The results of panel data analysis show that the economic growth variable has a significant and negative effect on the unemployment rate, the HDI has no significant and negative effect on the unemployment rate, the Regency/City Minimum Wage (UMK) variable has a positive and significant effect on the unemployment rate, and population has a significant and significant effect on the unemployment rate. negative on the unemployment rate and together the economic growth variables, Human Development Index (HDI), Regency/City Minimum Wage (UMK) and population have a significant effect on unemployment on the island of Java.